Sonorous identities of the Bolivian afrodescendants. (Revista Argentina de Musicología, 2008)
An approximation to the sonorous identities of the Bolivian afro-descendants undertaken from two perspectives -a historical perspective, and a contemporary one. The guidelines of this study are: 1) How has the sonorous identity of the Afro-Bolivians been constructed since the colonial period until the present? 2) How does this sonorous identity find expression nowadays? This paper considers identity as an ongoing and contextual relationship and therefore, never finished, centered or totally constituted. characterized rather by fluidity. Nonetheless. identity contains at the same time some elements that produce a notion of permanence through time. Within this perspective, we explore how music, musical instruments, singing, dances or some spaces as fellowships -"cofradía"- and religious festivities have become key devices in the construction and narrative of the identity of this important community almost invisible in Bolivia until now.
Keywords: sonorous identities; Afro-descendants; Bolivia; musical expressions